2019
DOI: 10.15441/ceem.18.060
|View full text |Cite
|
Sign up to set email alerts
|

Worsened survival in the head-up tilt position cardiopulmonary resuscitation in a porcine cardiac arrest model

Abstract: ObjectiveHead elevation at an angle of 30° during cardiopulmonary resuscitation (CPR) was hemodynamically beneficial compared to supine position in a previous porcine cardiac arrest experimental study. However, survival benefit of head-up elevation during CPR has not been clarified. This study aimed to assess the effect of head-up tilt position during CPR on 24-hour survival in a porcine cardiac arrest experimental model.MethodsThis was a randomized experimental trial using female farm pigs (n=18, 42±3 kg) sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…There remain several caveats regarding the safety of the head-up approach. Our own laboratory work, and that of others, have led us to believe that the head-up process should only begin after several minutes of providing traditional supine CPR with the ITD applied to help “prime the pump” (28, 29). It is further recommended that tilting should be implemented gradually, in a specific sequence following the “priming” step, and only with concurrent use of an ITD in particular (2831).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remain several caveats regarding the safety of the head-up approach. Our own laboratory work, and that of others, have led us to believe that the head-up process should only begin after several minutes of providing traditional supine CPR with the ITD applied to help “prime the pump” (28, 29). It is further recommended that tilting should be implemented gradually, in a specific sequence following the “priming” step, and only with concurrent use of an ITD in particular (2831).…”
Section: Discussionmentioning
confidence: 99%
“…Our own laboratory work, and that of others, have led us to believe that the head-up process should only begin after several minutes of providing traditional supine CPR with the ITD applied to help “prime the pump” (28, 29). It is further recommended that tilting should be implemented gradually, in a specific sequence following the “priming” step, and only with concurrent use of an ITD in particular (2831). The main admonition is to avoid going directly to the full-tilt target at the beginning of resuscitation efforts and to use appropriate accompanying adjuncts to enhance circulation as described in this analysis considering that it otherwise may even be harmful hemodynamically (2831).…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 studies [13,19,21] with 50 participants reported the ROSC rate. The ROSC rate was 50% (12/24) in the HUP group and 58%…”
Section: Rosc Ratementioning
confidence: 99%
“…In addition, facilitating venous return may increase CoPP, and a higher CoPP is associated with a higher ROSC rate [12]. However, Park YJ et al demonstrated that head-up CPR could worsen the survival rate [13]. The outcome of head-up CPR seems inconclusive, so clarifying the effect of head-up CPR is important.…”
Section: Introductionmentioning
confidence: 99%
“…With great interest, we have read the article by Park et al 1 published in Clinical and Experimental Emergency Medicine. This article shows that a 30° angle head-up positioned cardiopulmonary resuscitation (CPR) resulted in a lower 24-hour survival rate and return of spontaneous circulation rate compared with conventional supine positioned CPR.…”
Section: Dear Editormentioning
confidence: 99%